Research and Application of Globally Optimized Sequence Stratigraphic Seismic Interpretation Technology: Taking the Lower Cretaceous Shahezi Formation of Xujiaweizi Fault Depression as an Example. (15th September 2021) - Guan, Xiaowei; Meng, Qian; Jiang, Chuanjin; Liu, Xinyu; Han, Menglu
Abstract : In the study of sequence stratigraphy in continental rift basins, the use of seismic data to track different levels of sequence stratigraphic boundaries laterally is the key to the division of sequence stratigraphic units at all levels and the establishment of an isochronous sequence stratigraphic framework. Traditional seismic interpretation and the establishment of a 3D sequence stratigraphic structure model are a difficult research work. This paper introduces the concept of cost function minimization and performs global stratigraphic scanning on 3D seismic data to interpret horizons and faults in a large grid. Constrained by the results, human-computer interactive intelligent interpretation, by adding iterative interpretation of geological knowledge, established a global stratigraphic model with a relative geological age. The application in the Lower Cretaceous Shahezi Formation of Xujiaweizi fault depression shows that this technology has improved the accuracy and efficiency of sequence stratigraphic interpretation, and the application of this technology has achieved the interpretation of each event horizon under the current seismic data resolution conditions. In this way, a continuous sequence stratigraphic model is established. From this stratigraphic model, any high-frequency sequence-interpreted seismic horizon can be extracted, which provides a basis for the combination of lateral resolution and longitudinal resolution of subsequent reservoir prediction.